Factors Determining Organic Farming Adoption: International Research Results and Lessons Learned for Indonesia - nFN Ashari; Juwaidah Sharifuddin; Mohamed Zainal Abidin (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2017)
Indonesia is potential to develop organic farming as it has suitable land and supporting technology. Demand for organic product is supposed to increase in the future due to people’s awareness about safety and healthy food. It implies that organic farming has a good prospect to develop as agriculture-base business. However, it seems that farmers’ response to adopt organic farming technology is very low indicated by low rate of adoption. Actually, many countries have experiences in term of organic farming. This paper aims to assess determinant factors of organic farming adoption based on international research experiences and to withdraw lessons learned to raise adoption rate in Indonesia. The results showed that the determinant factors of organic farming adoption consisted of various aspects, i.e. (1) information and knowledge availability, (2) economic and financial motives, (3) technical and management skills, (4) social consideration, (5) environmental concern, (6) institutional environment, and (7) farmers’ socio-economic and demographic background. Accordingly, those aspects should be taken into account in policy formulation to encourage organic farming adoption. Indeed, government’s role is very crucial, mainly to convince farmers about organic farming benefit and to provide information as well as technical assistance. AbstrakIndonesia memiliki potensi besar untuk mengembangkan pertanian organik karena tersedia lahan dan teknologi pendukungnya. Permintaan produk organik juga diperkirakan meningkat pada masa mendatang seiring dengan meningkatnya kesadaran masyarakat tentang pangan yang aman dan sehat. Hal ini menyiratkan bahwa pertanian organik memiliki prospek bagus sebagai bisnis berbasis pertanian. Namun, nampaknya respon petani untuk mengadopsi teknologi pertanian organik sangat lambat yang ditunjukkan oleh rendahnya tingkat adopsi. Sebetulnya banyak negara yang memiliki pengalaman dalam adopsi pertanian organik seperti dikemukakan sejumlah literatur. Tujuan makalah ini adalah untuk mengetahui faktor penentu adopsi pertanian organik berdasarkan pengalaman penelitian di manca negara dan menarik pelajaran untuk meningkatkan tingkat adopsi di Indonesia. Sumber literatur adalah hasil hasil penelitian terkait dengan adopsi pertanian organik baik di negara maju maupun berkembang. Hasil tinjauan menunjukkan bahwa faktor penentu adopsi pertanian organik terdiri dari berbagai aspek, yaitu (1) tersedianya informasi dan pengetahuan, (2) motif ekonomi dan keuangan, (3) keterampilan teknis dan manajemen, (4) pertimbangan sosial, (5) kepedulian lingkungan, (6) lingkungan kelembagaan, dan (7) latar belakang sosial ekonomi dan demografi petani. Dengan demikian, untuk mendorong adopsi pertanian organik sejumlah aspek tersebut harus dipertimbangkan dalam perumusan kebijakan dan program. Peran pemerintah sangat penting terutama untuk meyakinkan petani tentang manfaat pertanian organik, penyediaan informasi, maupun bantuan teknis bagi petani